Cryptography In Communication System Via Gupta Integral Transform - Gupta, Rahul; Gupta, Rohit; Verma, Dinesh (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Cryptography is a critical approach to secure data transmission and protection for authentication and privacy. It is a discipline related with communication system confidentiality. Recently, integral transform approach has been employed by many researchers to increase the power of encryption and decryption processes in cryptography. A group of practices known as information security are meant to stop unwanted access or changes to data. Cryptography is the sole thing preventing the hacker from reading protected data if they are able to bypass the security firewall, passwords, and other precautions put in place to keep them out. Thus, cryptography aids in data protection for both individuals and organizations. In order to prevent the ciphertext from being utilized for plaintext replication without the corresponding key, cryptography aims to transform plaintext into ciphertext that may be communicated across insecure communication channels. The number of multiples of mod n serves as the key in the newly designed cryptographic technique in the proposed work, which makes use of the Gupta transform. As a result, any kind of attack by an eyedropper finding the key would be exceedingly tough. The integral Gupta transform uses the symmetric cryptosystem where the key must stay secret and shared between the involved parties only to encrypt the transmitted plaintext. The Inverse integral Gupta transform is used to decrypt the received ciphertext back into its original context. The ability of integral Gupta transform is exhibited for the encryption and decryption processes in cryptography and in general, in the area of data security with the help of a practical application.